Rhodium complex with unsymmetrical vicinal diamine ligand: excellent catalyst for asymmetric transfer hydrogenation of ketones - Deshpande, Sudhindra H.; Shende, Vaishali S.; Shingote, Savita K.; Chakravarty, Debamitra K.; Puranik, Vedavati G.; Chaudhari, Raghunath V.; Kelkar, Ashutosh A. (RSC Advances, 2015)
New unsymmetrical vicinal diamine ligands with systematic variation in the regio and stereo positions in the amine and sulphonamide groups were synthesized from cheap starting material such as norephedrine. Catalytic Asymmetric Transfer Hydrogenation (ATH) of aromatic alkyl ketones has been investigated using transition metal complexes and new derivatives of monotosylated unsymmetrical vicinal diamine ligands using sodium formate as the hydrogen source, in water and methanol. Chiral secondary alcohols were obtained with excellent enantioselectivity (>95% ee) and conversion of ketones (>95%) with [Rh(Cp*)Cl-2](2) and ligand 4 as a catalyst. Enantioselectivity was found to be slightly higher with the use of methanol as a solvent for ATH of ketones with sodium formate as the hydrogen source compared to water as a solvent and was found to be consistent with all the ketones investigated. The reaction mixture is homogeneous in methanol unlike in water, where substrate and product are insoluble in water and form separate phase, sodium formate being soluble in water. The activity and enantioselectivity obtained for ATH of ketones using [Rh(Cp*)Cl-2](2) and unsymmetrical vicinal diamine ligand as catalyst was comparable with the C2 symmetric benchmark ligands like TsDPEN ((1R, 2R)-N-(p-tolylsulfonyl)-1,2-diphenylethylene- diamine), and TsCYDN ((1R, 2R)-N-(p-tolylsulfonyl)-1,2-cyclohexyl, diamine) under similar reaction conditions. To the best of our knowledge, this is first example of the ATH of ketones with good activity and high enantioselectivity with [Rh(Cp*)Cl-2](2) and unsymmetrical vicinal diamine ligands as catalyst systems.

Room-temperature asymmetric transfer hydrogenation of biomass-derived levulinic acid to optically pure gamma-valerolactone using a ruthenium catalyst - Shende, Vaishali S.; Raut, Amol B.; Raghav, Prathamesh; Kelkar, Ashutosh A.; Bhanage, Bhalchandra M. (ACS Omega, 2019)
This study presents a first report on ruthenium-catalyzed asymmetric transfer hydrogenation (ATH) of levulinic acid (LA) to chiral gamma-valerolactone (GVL). ATH of LA has been explored with Noyori's chiral catalyst (Ru-TsDPEN) in methanol solvent. Efficacy of ATH reaction of LA was investigated under different reactions conditions such as temperature, catalyst, and hydrogen donor concentration. The effect of various organic tertiary bases along with formic acid (FA) as a hydrogen donor was studied, and N-methylpiperidine with FA (1:1 molar ratio) was revealed as an efficient hydrogen donor for ATH of LA to GVL furnishing chiral GVL with complete conversion and 93% enantiomeric excess (ee). This operationally simple and mild ATH protocol was tested for practical applicability of ATH of LA obtained from biomass waste (rice husk and wheat straw) and furnished chiral GVL with 82% ee.